Comparative Study on HPSS Content in Current and Previous Chinese High School - He, Yuze (Science Insights Education Frontiers, 2025)
Chinese 2017 General High School Physics Curriculum Standards explicitly include understanding the nature of science (NOS) as core literacy for students. History, philosophy of science, and sociology of science (HPSS) education is an important way to promote students’ understanding of the nature of science. In this context, this study analyzed the content of HPSS in two physics textbooks before and after the promulgation of the new curriculum standards using a content analysis method based on the analytical framework of HPSS. The analysis compares the number and copiousness of HPSS content in the current high school physics textbooks published in 2019 and the previous edition of high school physics textbooks published in 2004. The presentation of this HPSS content was also analyzed. It was found that there was an increase in HPSS content in the new edition of the textbook compared to the old edition, mainly a decrease in the history of science content and an increase in both the philosophy of science and sociology of science content. The HPSS content copiousness was low in both the old and new editions of the textbook. Finally, the distribution of the respective sub-dimensions of the HPSS was very uneven.